Fig. 2 in Two New Species of Free-living Marine Nematodes (Nematoda: Axonolaimidae and Tripyloididae) from the Coast of Antarctica - Shimada, Daisuke; Suzuki, Atsushi C.; Tsujimoto, Megumu; Imura, Satoshi; Kakui, Keiichi (Zenodo, 2021)
Fig. 2. Odontophora odontophoroides sp. nov. A, B, E–J, differential interference contrast photomicrographs; C, D, SEM images. A, inner view of head (holotype); B, amphid and odontia (holotype); C, mouth opening with odontia (non-type male); D, amphidial aperture (nontype male); E, distal end of spicule with spine-like structures (holotype); F, ventral view of left spicule (white arrowheads) and gubernacula (black arrowheads) (dissected non-type); G, gubernaculum (holotype); H, precloacal pore (holotype); I, precloacal supplement (black arrowhead) (holotype); J, contents of testis (holotype); K, sperms in seminal vesicle (holotype). Scale bars: A–G, J, K, 10 µm; H, I, 5 µm. : Published as part of Shimada, Daisuke, Suzuki, Atsushi C., Tsujimoto, Megumu, Imura, Satoshi & Kakui, Keiichi, 2021, Two New Species of Free-living Marine Nematodes (Nematoda: Axonolaimidae and Tripyloididae) from the Coast of Antarctica, pp. 49-63 in Species Diversity 26 (1) on page 53, DOI: 10.12782/specdiv.26.49, http://zenodo.org/record/5736867